A Continent in Crisis: European Labor and the Fate of Social Democracy. (March 2018) - Schulze-Cleven, Tobias
Over the past decade, Europe has stumbled from crisis to crisis, shaking the confidence of observers in the continent's capacity to maintain the egalitarian societies and socially embedded markets that have long informed arguments for social democratic reforms in the United States. As tensions in democratic capitalism have intensified, many aspects of Europe's established political economic order have come under pressure. This review essay explores key causal processes behind the continent's predicament. It does so to illustrate challenges and opportunities for organized labor in Europe, and to call on social scientists to reengage with the class politics of capitalism.